Brisk Walking Exercise Sebagai Bagian dari Intervensi Holistic bagi Penderita Hipertensi di Puskesmas Setabelan - Fitria Shafa Salsabila; Farid Rahman; Yusuf Arianto (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Setabelan, a neighbourhood in the Banjarsari sub-district, houses a popular healthcare centre called Puskesmas Setabelan. Recent data shows that hypertension is the second most common reason for visits to the centre, with a total of 273 visits and eight patients daily. To address this issue, educational activities were organized to increase awareness and knowledge of physical exercise, particularly brisk walking, and the control of salt consumption among individuals with hypertension. These activities included distributing leaflets, presenting material, demonstrating exercises, and engaging in question and answer sessions with prolanis participants in Taman Banjarsari, Surakarta. The programme led to a significant increase in understanding, as evidenced by the pre-test average score of 2.18 and the post-test average score of 4.48, indicating an improvement of 2.30. The hope is that this community service initiative will empower participants with hypertension to independently manage their blood pressure effectively, ensuring the sustainability of the programme.